PENGELOLAAN ALOKASI DANA DESA UNTUK PEMBERDAYAAN MASYARAKAT: PERSPEKTIF MAQASHID SYARIAH - Agung Maulana; Ahmad Rizki Zulfikar Hilmi; Ayu Andini (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2019)
This study examines the concept of maqoshid al-Shariah in Alokasi Dana Desa (Allocation of Village Fund). Furthermore, ADD is the fund allocated by the National Government to the village in order to enhance the development of economic, social and infrastructure the villages. Through the ADD, Village administrators have authority to manage the independently the development of the village based on the local villagers. The concept of maqoshid al-Syariah in this research used to analyze the implementation of ADD in Desa Cilebut Barat, Kabupaten Bogor. The objective of this research is to examine the effectiveness of Cilebut Barat Village Administrator in order to manage the Village Fund based on the maqoshid al-Syariah perspective. This reseach complies the qualitative methode using the primary and secondary data. The Findings of this research are1) the Allocation of Village Fund in Cilebut Barat has been distributed well, effective. The Fund used by the village administrator fulfills the requirement, prosedures. 2) the absorption of village fund to facilitate the village programs is achieved optimally. 3)The Alacotion of Village Fund in Desa Cilebut complies to the maqoshid Syariah, this is proveed with the distribution of the fund fulfill the all elements of maqoshid Syariah.